Firm Value Drivers in Indonesian Food and Beverages Sector: Faktor-Faktor yang Mempengaruhi Nilai Perusahaan pada Sektor Makanan dan Minuman: Bukti dari Bursa Efek Indonesia - Yenny Wulansari; Eny Maryanti (Academia Open, 2023)
This quantitative study investigates the impact of several key factors on the firm value of food and beverages companies listed on the Indonesia Stock Exchange (IDX) during the period of 2016-2020. The study focuses on the effects of Payable Account Policy, Managerial Ownership, Intellectual Capital, Audit Committee, and Liquidity on firm value. Purposive sampling was employed to select a sample of eight companies from a population of 26, and data was collected through documentation methods. The findings reveal that Account Payable (Debt to Equity Ratio) positively influences firm value, while Managerial Ownership and Liquidity have negative effects on firm value. Intellectual Capital and the presence of an Audit Committee were found to have no significant impact on firm value. These results have important implications for both researchers and practitioners in understanding the factors that drive firm value in the dynamic food and beverages industry. Highlights: The study examines the impact of multiple factors on firm value in the food and beverages sector listed on the Indonesian Stock Exchange. Managerial ownership and liquidity were found to have negative effects on firm value, while the payable account policy (debt to equity ratio) had a positive effect. Intellectual capital and the presence of an audit committee were not found to significantly affect firm value, emphasizing the need for further research in these areas. Keywords: Firm Value, Food and Beverages Sector, Indonesian Stock Exchange, Factors, Influence.